A nature-inspired feature selection approach based on hypercomplex information - Rosa, Gustavo H. de [UNESP]; Papa, Joao P. [UNESP]; Yang, Xin-She (Elsevier B.V., 2020)
Feature selection for a given model can be transformed into an optimization task. The essential idea behind it is to find the most suitable subset of features according to some criterion. Nature-inspired optimization can mitigate this problem by producing compelling yet straightforward solutions when dealing with complicated fitness functions. Additionally, new mathematical representations, such as quaternions and octonions, are being used to handle higher-dimensional spaces. In this context, we are introducing a meta-heuristic optimization framework in a hypercomplex-based feature selection, where hypercomplex numbers are mapped to real-valued solutions and then transferred onto a boolean hypercube by a sigmoid function. The intended hypercomplex feature selection is tested for several meta-heuristic algorithms and hypercomplex representations, achieving results comparable to some state-of-the-art approaches. The good results achieved by the proposed approach make it a promising tool amongst feature selection research. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Meta-heuristic optimization; Hypercomplex spaces; Feature selection